Beberapa Karakteristik dan Perilaku Pedagang Pemasaran Komoditas Hasil-hasil Pertanian di Indonesia (Forum Penelitian Agro Ekonomi, 2016)
EnglishTrading and marketing activities related to agricultural commodities generate ambivalence attitude to their actors. In the positive perspective, these probably have an important role, especially as a prime move of agribusiness system. The other side, they are frequently cause some obstacles in developing the agribusiness system; i.e. causing unfairly benefit sharing and inefficiency in the agribusiness system. This paper describes characteristics and behavior of agricultural traders in Indonesia, especially in the social system framework. The subjects of this paper are taken from various research results on agribusiness. Results of this paper are (1) in the agricultural marketing activities usually it can be found three categories of traders which are real trader, stooge trader, and commission trader; and (2) the marketing structure configurations are mostly developed by interpersonal relation and interpersonal trust among agribusiness actors; and (3) among the traders of agricultural commodities, it frequently can be found higher spirit of solidarity compared to that of trader and farmer. In order to develop agribusiness system more comprehensively and efficiently, it is important to understand more deeply and fairly how to generate the benefit sharing equally on their actors. IndonesianPekerjaan perdagangan menimbulkan sikap ambivalen bagi pelakunya, yaitu pada sisi positif mereka adalah sebagai motor penggerak sistem agribisnis, namun sebaliknya (sekaligus) pada sisi yang negatif, mereka dianggap sebagai penyebab kekurangadilan serta inefisiensi sistem agribisnis. Tulisan ini merupakan kajian sistem sosial pedagang hasil pertanian. Bahan tulisan berasal dari penelitian-penelitian agribisnis berbagai komoditas pertanian, terutama keragaan subsistem pemasaran dan perilaku pedagang di dalamnya. Beberapa hasil yang dapat dikemukakan adalah: Pertama, kegiatan pemasaran hasil pertanian dilakukan oleh tiga golongan perdagang yaitu pedagang, pedagang kaki tangan dan pedagang komosioner. Kedua, bangunan jaringan tata niaga disndarkan pada sikap saling mempercayai melalui pola interaksi yang cenderung tetap (langganan). Ketiga, dijumpai adanya solidaritas sesama pedagang yang lebih tinggi daripada solidaritas pedagang dengan para pemasok (petani, epternak dan nelayan). Implikasi dari temuan tersebut, maka pembangunan agribisnis secara utuh perlu pemahaman yang lebih mendalam dan proporsional terhadap pedagang dalam rangka melakukan pemberdayaan terhadap subsistem pemasaran demi sistem agribisnis itu sendiri, serta untuk menjamin perolehan yang lebih adil pada seluruh pelakunya.
Keywords: trader; marketing; agricultural product; pedagang; pemasaran; hasil pertanian